Continuing Qualitative Data Collection During the COVID 19 Pandemic: Lessons Learnt from A Study Among Tribes in Manipur, India - Saritha Nair; Meena Hijam; Nongzaimayum Tawfeeq Alee; Nirendra Haobijam; Harpreet Kaur; M. Vishnu Vardhana Rao (Medsci Publications, 2022)
COVID-19 pandemic has caused disruptions in carrying out research activities in the field. The established methods of data collection for both qualitative and quantitative research could not be implemented. Researchers worldwide adopted contactless data collection methods, including the use of mobile phones for research purposes. This paper presents the experiences of conducting interviews among tribal population using mobile phones in three villages of Manipur during the pandemic. The interviews proved to be successful and effective. Minor technical glitches were a challenge but were not significant to affect the quality of the data. During unprecedented times such as the current pandemic, conducting interviews via mobile phones could be a viable alternative to face-to-face interviews for collecting qualitative data from the communities.